President Xi Jinping's Use of Persuasion Techniques in His BRI Program Speech Text - Rosita Nugraheni; Subandi Subandi; Xinyue Lin (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2026)
This study ivestigates the use of persuasive techniques in Chinese President Xi Jinping’s speeches delivered to promote the Belt and Road Initiative (BRI).  This study aims to identify the forms of persuasion employed and to understand how Xi Jinping constructs his image and influences his audience to accept the BRI concept consciously and without resistance. The study is based on the view that a speech is a persuasive discourse requiring careful selection of language, techniques, and communication strategies to ensure that the message is received in line with the audience’s values and moral beliefs. The analysis of the speech data reveals 119 instances of persuasion, classified into six types of techniques: rationalization, identification, suggestion, conformity, compensation, and projection. Rationalization is used to build logical justification for the BRI concept; identification emphasizes shared viewpoints between the speaker and the audience;  suggestion functions to persuade through the emotional use of imperative diction ; conformity creates a sense of equality and togetherness; compensation highlights transformation toward a better condition; while projection is employed to position China as a positive and open actor, subtly shifting negative impressions toward others. The findings indicate that Xi Jinping strategically employs language and persuasive techniques to deliver political and economic messages within a framework of humanistic, harmonious, and low-conflict communication. These techniques strengthen China’s image as an inclusive global leader that promotes shared benefits through the BRI program.